Kingdom of the Netherlands-Netherlands Antilles : Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This review of financial sector regulation and supervision in the Kingdom of the Netherlands-Netherlands Antilles explains banking, insurance, and pension fund supervision. The Netherlands Antilles is resolved to remove the perception created by placement of the jurisdiction in the weakest category of the list of offshore financial centers, published by the Financial Stability Forum (FSF). Bank of the Netherlands Antilles (BNA) staff is highly capable, well-trained, and dedicated, and is able to attract appropriate personnel and material resources to perform its functions.